Comparative study of conservation management between Kelantan and Pulau Pinang / Mohd Zulkifli Mohd - Mohd, Mohd Zulkifli (2005)
Conservation and preservation of old buildings is one of the current concerns within the buitt environment of our nation. It is realised that these buildings have important significance and contribution to our nation's historical development. Unfortunately, most of tl1e problems affected these buildings during post gazetted period. These problems arise due to building protection and maintenance management has not been emphasized by current related conservation law and gUidelines, or by organizations or parties tl1at are responsible for tl1e maintaining of tl1ese buildings. Many old buildings in Kota Bharu face these problems which greatly affect tl1e building's performance and condition, structure stabilization and building character. Therefore, there is a greater possibility that Malaysian could loose their cultural significant and heritage value of these old buildings owing to the related organization orparties thatare involved and responsible in their conservation and maintenance management are unable, fail or ignore to apply suitable and appropriate ways or method to protect and maintain them. Heritage relates to the remains of the past, which arguably should be maintained for national pride and be cherished throughout the future generations. Urban conservation refers to their protection and preservation of their elements of urban heritage from being demolished or restored without proper and systematic planning, control and management measures. Examples of their elements of urban heritage are buildings of significant architectural values, historical sites and the uniqueness of the local cultures. Such elements are commonly found in many heritage cities. Apart from being national treasures, these heritage elements should be promoted as tourism products. This dissertation highlights the two heritage cities of Malaysia, namely Georgetown and Kota Sharu, with an emphasis on their heritage bUildings, historical sites and unique local cultures. It also discusses aspects of urban tourism, tourism and heritage marketing, urban conservation, elements of city image; and efforts carried out by the local authorities and the local community to accentuate their heritage products lor the promotion of tourism